‘Ghost’ stories: sociocultural factors influencing tuberculosis treatment adherence in Ghana - Salifu, Yakubu; Eliason, Cecilia; Mensah, George (RCN Publishing, 2016)
Background: Non-adherence to treatment is a major problem in tuberculosis (TB) control and leads to adverse outcomes and increased morbidity and mortality. Aim: To explore the experiences of TB patients taking anti-TB drugs in Ghana to improve treatment adherence and prevent TB. Method: Ten semi-structured interviews were conducted. Participants were asked about their experience of taking anti-TB drugs and factors that affect treatment adherence. These were transcribed and analysed using inductive content analysis. Participants were chosen through purposive sampling. Findings: Three main themes emerged from the data: family support, stigma, beliefs and misconception. Subthemes included emotional support, financial difficulty and myth. Conclusion: Patients who have family support, who are ‘policed’ and reminded to take their drugs at home are likely to adhere to treatment. Traditional beliefs and social stigma can affect medication adherence adversely.